Fetal pain - Rokyta, Richard (Neuro endocrinology letters, 2008)
The fetus reacts to nociceptive stimulations through different motor, autonomic, vegetative, hormonal, and metabolic changes relatively early in the gestation period. With respect to the fact that the modulatory system does not yet exist, the first reactions are purely reflexive and without connection to the type of stimulus. While the fetal nervous system is able to react through protective reflexes to potentially harmful stimuli, there is no accurate evidence concerning pain sensations in this early period. Cortical processes occur only after thalamocortical connections and pathways have been completed at the 26th gestational week. Harmful (painful) stimuli, especially in fetuses have an adverse effect on the development of humans regardless of the processes in brain. Moreover, pain activates a number of subcortical mechanisms and a wide spectrum of stress responses influence the maturation of thalamocortical pathways and other cortical activation which are very important in pain processing.
Keywords: gestační stáří; Animals; plod; Female; Fetal Development; Pain Threshold; Gestational Age; Perception; ženské pohlaví; vývoj plodu; percepce; lidé; Fetus; Neural Pathways; těhotenství; bolest; Central Nervous System; nervové dráhy; krysa rodu Rattus; Pain; zvířata; centrální nervový systém; Pregnancy; práh bolesti; Rats; Humans